Relações raciais e empreendedorismo: um estudo sobre negros empreendedores na região metropolitana do Rio de Janeiro - Santos, Edy Lawson Silva (2017)
This research aims at understanding the racial influences in the constitution of enterprises by black people in the metropolitan region of Rio de Janeiro. It is our intention to approach these two theoretical categories, race and entrepreneurship, due the theoretical and empirical gap of existing research in the Business Administration area concerning the proposed topic. Although entrepreneurship has consolidated itself as a research area in the field of Business Administration studies, race, as theme, is still unexplored by the investigations developed in this area. In this study, I present as a theoretical contribution a discussion on the effects of race in the constitution of entrepreneurial processes conducted by black people in Brazil. The qualitative research was conducted through half-structured interviews with entrepreneurs. The research results were analyzed under the technique of interpretive analysis for qualitative research for studies that have empirical basis, aiming to identify conceptual categories that enable understanding of how race can be related with entrepreneurship in Brazil. The categorization was made according to the entrepreneurial process model proposed by Baron and Shane (2015). Nine black entrepreneurs were interviewed. These entrepreneurs run different businesses in the metropolitan region of Rio de Janeiro. The interviews have collected the perceptions of each respondent about race, entrepreneurship and a bit of their life stories. These interviews, in addition to the researcher's experiences and perceptions and his records, composed the empirical part of the study. As a result, the study shows that the construction of race and the "place" of black people have great impact on the life and in the enterprise of each respondent, in motivation, in the identification of the business opportunity and in the meaning of their own work.